PENGARUH KECERDASAN EMOSIONAL DAN EFIKASI DIRI TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS XI IPS DI SMAN 41 JAKARTA - Nur Aini Azizah; I Ketut R Sudiarditha; Aditya Pratama (International Journal of Multidisciplinary Research and Literature, 2022)
Critical thinking skill is a cognitive process involving one's mind to integrate knowledge in analysing information and determining solutions to existing problems according to data and facts to produce the right decisions. This study aimed to determine whether emotional intelligence and self-efficacy affect the critical thinking skills of XI IPS students at SMA Negeri 41 Jakarta in economics. This research is quantitative research with an explanatory survey method. The sampling technique used is proportional random sampling with a sample of 84 class XI IPS SMAN 41 Jakarta students. The data collection for emotional intelligence and self-efficacy using a questionnaire, while the critical thinking skills using an objective assessment test. The results of this study indicate that emotional intelligence has a positive and significant effect on students' critical thinking skills, and self-efficacy has a positive and significant effect on students' critical thinking skills. Emotional intelligence and self-efficacy simultaneously positively and significantly affect students' critical thinking skills. This study's results imply that students' emotional intelligence and self-efficacy can improve their critical thinking skills